Optimalisasi Pojok Baca: Strategi Efektif Meningkatkan Minat Baca Siswa di MI Darul Muta'allimin Patianrowo Nganjuk - Moh. Ali Fauzi; Mukhamat Saini; Luluk Indarinul Mufidah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2025)
This study aims to evaluate the optimization strategies of reading corners in increasing students' reading interest at MI Darul Muta'allimin Patianrowo Nganjuk. The research utilizes a descriptive qualitative method, with data collection techniques including interviews, observations, and documentation. Results indicate that the active role of teachers in motivating and guiding students effectively enhances reading interest. However, limited access to relevant and engaging books presents a primary challenge in managing the reading corner. Support from parents and literacy communities also plays a crucial role in enriching reading materials. Additionally, a comfortable and attractive reading corner environment, along with structured and regular literacy programs, positively influences students' interest in reading activities. Optimizing the reading corner through increased teacher involvement, appealing reading spaces, and parental engagement is expected to sustainably improve students' reading interest and literacy skills. This study concludes that reading corner optimization with collective support from various parties can be an effective strategy for fostering a culture of literacy among students at MI Darul Muta'allimin